(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
Angiosperms at Gobindaganj Upazila of Gaibandha district, Bangladesh was studied from January to December 2018. An extensive floristic survey and angiosperms collection have been made throughout the study area. A total of 295 species belonging to 246 genera under 89 families were recorded. Plant habit analysis shows that herbs, shrubs, climbers and trees are represented by 47.45%, 15.93%, 12.20% and 24.40%, respectively. Distribution of angiosperm species in the families shows variation. Asteraceae is the most dominant family represented by 25 species, followed by Fabaceae (19 species), Euphorbiaceae (18 species), Cucurbitaceae (17 species), Acanthaceae (11 species), Solanaceae (11 species), Amaranthaceae (10 species) and Apocynaceae (10 species). 44 families are represented by a single species each while 37 families are represented by 2 to 8 species each. Status of occurrence has been recorded for proper conservation management and sustainable utilization of the taxa which show 218 (73.89%) to be common, 63 (21.35%) as rare, 10 (3.38%) as vulnerable, and 4 (1.35%) are found as endangered in the study area. For each species scientific name, voucher number, Bangla name, English name, habit, status of occurrence and flowering time were recorded.